2017
DOI: 10.1007/s10522-017-9685-9
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins, a promising target in slowing down the ageing process

Abstract: Ageing is a plastic process and can be successfully modulated by some biomedical approaches or pharmaceutics. In this manner it is possible to delay or even prevent some age-related pathologies. There are some defined interventions, which give promising results in animal models or even in human studies, resulting in lifespan elongation or healthspan improvement. One of the most promising targets for anti-ageing approaches are proteins belonging to the sirtuin family. Sirtuins were originally discovered as tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
278
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(285 citation statements)
references
References 244 publications
(322 reference statements)
3
278
0
4
Order By: Relevance
“…Because of the essential role of the NAD + /sirtuin pathway in the metabolic regulation of aging (Grabowska, Sikora & Bielak‐Zmijewska, 2017), we hypothesized that the overexpression of NQO1 and CYB5R3, two NAD + ‐producing enzymes, may affect either NAD + metabolism, sirtuin expression and/or activity, or both. As expected, NAD + and NADP + levels were significantly higher in RedTg vs. Wt muscle (Figure 4a), accompanied by an accumulation of SIRT1 protein and a trend toward lower total lysine‐acetylated protein levels in RedTg muscle (Figure 4b,c).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the essential role of the NAD + /sirtuin pathway in the metabolic regulation of aging (Grabowska, Sikora & Bielak‐Zmijewska, 2017), we hypothesized that the overexpression of NQO1 and CYB5R3, two NAD + ‐producing enzymes, may affect either NAD + metabolism, sirtuin expression and/or activity, or both. As expected, NAD + and NADP + levels were significantly higher in RedTg vs. Wt muscle (Figure 4a), accompanied by an accumulation of SIRT1 protein and a trend toward lower total lysine‐acetylated protein levels in RedTg muscle (Figure 4b,c).…”
Section: Resultsmentioning
confidence: 99%
“…Sirtuins are considered among the most promising targets for modulating aging-associated cellular and molecular processes and disease pathologies [41]. They have been shown to promote longevity in species across multiple taxonomic groups in response to caloric restriction or activation with molecules such as resveratrol [35, 4247].…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
“…They have been shown to promote longevity in species across multiple taxonomic groups in response to caloric restriction or activation with molecules such as resveratrol [35, 4247]. Multiple studies have shown declines in SIRT activity or levels with age in different organisms, tissues, and cells types [41, 4852]. SIRT6 and SIRT7 knockout mice display progeroid phenotypes and have shorter lifespans than controls [53, 54], and SIRT3 polymorphisms have been associated with longevity in human populations [55].…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
“…SIRT1 exhibits a variety of functions in many organisms. The enzyme exerts anti-ageing actions and is involved in calorie restriction, DNA repair and inhibition of inflammation (Baur et al 2006, Zhang et al 2010, Grabowska et al 2017.…”
Section: Introductionmentioning
confidence: 99%